The relationship between office ergonomics and employees' performance at Universiti Teknologi MARA Machang / Nurazlyana Tazah - Tazah, Nurazlyana (2013)
Ergonomics is the scientific study of human work. It considers the physical and mental and limits or the worker as he or she interacts with tools, equipment, work methods, tasks and the working environment. Office ergonomics is the branch or ergonomics dealing specifically with the office environment. In recent years the main focus of office ergonomics has been on computer work due to the rapid in crease in computer use in the modem office and the associated increase and injuries. This research focused on the increasing rates and awareness or illness and injury occurred in the office on a regular basis that may affect the employees' performance. The objectives of the study was to identify the types of office ergonomics provided by Universiti Teknologi MARA Machang, to investigate the potential symptoms and injuries that may affect the performance of the employees in Universiti TeknoJogi MARA Machang and to investigate the relationship between office ergonomics and employees' performance at Universiti Teknologi MARA Machang. About 70 questionnaires were distributed among employees who worked in Universiti Teknologi MARA Machang, Kelantan Darul Naim. The response rate was 71.4% . The data collection used in the study was questionnaire. The study has showsthat the Universiti Teknologi MARA Machang takes office ergonomics as one of important aspects in order to improve their employees' performance. Universiti Teknologi MARA Machang was aware about the problem that they might face by not implementing office ergonomics. Based on the findings, it was concluded that Universiti Teknologi MARA Machang is a safe place for employees to work . The results obtained by the researcher shows that employees ' opinions stated mostly that there were only low and moderate potential symptoms and injuries that may affect their performance. The study also shows that there is a relationship between office design, office furniture and office environment and the employees performance at Universiti Teknologi MARA Machang. In the end, the study has provided several recommend actions in order to increase the practices of office ergonomics as well to improve the quality of their working environment.